2022
DOI: 10.1002/jbt.23114
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of trimetazidine against ovary ischemia–reperfusion injury via the TLR4/Nf‐kB signal pathway

Abstract: Late diagnosis and treatment of ovarian ischemia can lead to worsening of ischemia, irreversible damage to ovarian functions and infertility. In this process, there is no approved medical treatment that can reduce the negative effects of ischemia and contribute positively to ovarian functions during reperfusion after detorsion. Rats were randomly assigned into one of six groups of eight animals each. The groups were designed as follows: The control group, The ischemia(I) group, The Ischemia + Trimetazidine (I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Based on our observations, another affirming finding is the difference in TBARS level for determined lipid peroxidation-a process by which free radicals destroy lipids' carbon-carbon double bonds [7], which were elevated in the IR group and reduced in the C and IR-PRO groups. Our TBARS results align with those in the literature [27,28].…”
Section: Discussionsupporting
confidence: 93%
“…Based on our observations, another affirming finding is the difference in TBARS level for determined lipid peroxidation-a process by which free radicals destroy lipids' carbon-carbon double bonds [7], which were elevated in the IR group and reduced in the C and IR-PRO groups. Our TBARS results align with those in the literature [27,28].…”
Section: Discussionsupporting
confidence: 93%
“…Ozturk et al studied role of NF-κB in ovarian IR. The authors found that, after IR, oxidative stress and inflammation were increased and these cellular events upregulated the expression of NF-κB in IR groups 20 . A similar study was done by Deniz et al In their ovarian IR injury model on animals, they found NF-κB expression was increased in ovarian tissues 21 .…”
Section: Discussionmentioning
confidence: 98%